Overexpression in Plasmodium falciparum of an intrinsically disordered protein segment of PfUT impairs the parasite’s proteostasis and reduces its growth rate - Avalos-Padilla, Yunuen; Bouzón-Arnáiz, Inés; Ramírez, Miriam; Camarero-Hoyos, Claudia; Orozco-Quer, Marc; M. Arce, Elsa; Muñoz-Torrero, Diego; Fernàndez-Busquets, Xavier (Frontiers in Cellular and Infection Microbiology, 2025)
The proteome of Plasmodium falciparum exhibits a marked propensity for aggregation. This characteristic results from the parasite’s AT-rich genome, which encodes numerous proteins with long asparagine-rich stretches and low structural complexity, which lead to abundant intrinsically disordered regions. While this poses challenges for the parasite, the propensity for protein aggregation may also serve functional roles, such as stress adaptation, and could therefore be exploited by targeting it as a potential vulnerable spot in the pathogen. Here, we overexpressed an aggregation-prone segment of the P. falciparum ubiquitin transferase (PfUTf), an E3 ubiquitin ligase protein that has been previously demonstrated to regulate the stability of parasite proteins involved in invasion, development and drug metabolism. Overexpression of PfUTf in P. falciparum had evident phenotypic effects observed by transmission electron microscopy and confocal fluorescence microscopy, increased endogenous protein aggregation, disrupted proteostasis, and caused significant growth impairment in the parasite. Combined with dihydroartemisinin treatment, PfUTf overexpression had a synergistic effect that further compromised the parasite´s viability, linking protein aggregation to proteasome dysfunction. Changes in the distribution of aggregation-prone proteins, shown by the altered subcellular fluorescent pattern of the new investigational aggregated protein dye and antiplasmodial compound YAT2150 in the overexpressing P. falciparum line, highlighted the critical balance between protein aggregation, stress responses, and parasite viability, suggesting proteostasis-targeting therapies as a good antimalarial strategy.